PEMBERDAYAAN KELOMPOK SEBAYA DAN KONSELING DI SMP WIDYA SAKTI UNTUK MENINGKATKAN GERAKAN SEHAT REPRODUKSI REMAJA - Sri Ratna Dewi; Desak Putu Oki Lestari; , Ni Wayan Armerinayanti; I Wayan Suwarna (UNHI Press, 2019)
Adolescent are a transition period and highly sensitive to the influence of new values. The problems they face are also quite complex, one of which concerns reproductive health. Some studies suggest that peers are the most dominant factor in influencing the adolescent reproductive health behaviors. This dedication activity aims to increase adolescent knowledge and activate the role of peers and counseling teachers in disseminating correct information about reproductive health. The method of implementing activities in the form of providing material on adolescent reproductive health by a talk from the expert, training and mentoring to peer groups in carrying out mini counseling, as well as training and counseling for counseling teachers. After the implementation of this program obtained increased peer group knowledge and counseling teachers on adolescent reproductive health respectively as much as 50% and 30.8%. In addition, all peer groups are able to conduct mini-counseling as well as to do better counseling. Through this activity it is hoped that peer group partners and counseling is able to play an active role in continuously spreading information about adolescent reproductive health so that it can produce other peers who help keep the healthy atmosphere of the adolescents.